Analisis Politik Hukum Terhadap Peraturan Presiden Nomor 121 Tahun 2024 - Ramadani, Iko; Ismidar, Ismidar; Sembiring, Tamaulina (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2024)
ABSTRACT:At the end of his term, President Joko Widodo signed Presidential Regulation (Perpres) Number 121 of 2024 concerning Guarantee for Health Maintenance of Retired Ministers of State. The regulation regulates health insurance for former ministers and cabinet secretaries and their families, with costs borne by the State Revenue and Expenditure Budget (APBN). This regulation must be reviewed considering that the Minister of State also receives a pension as stated in Government Regulation Number 50 of 1980 Article 10 which reads that the Minister of State who resigns with honor from his position is entitled to a pension. This can cause discrimination because there are still many people, especially in remote and border areas who have not received basic health services, one of which is due to the limited budget for the health sector. The purpose of this study is to analyze the legal politics resulting from the issuance of Presidential Regulation Number 121 of 2024 concerning Guarantee for Health Maintenance of Retired State Ministers with the problem approach method used by the researcher is normative juridical with a legislative review approach.Keywords: Politics, Pretrial Regulations, Health Maintenance GuaranteeABSTRAKPada akhir masa jabatannya, Presiden Joko Widodo menandatangani Peraturan Presiden (Perpres) Nomor 121 Tahun 2024 tentang Jaminan Pemeliharaan Kesehatan Purnatugas Menteri Negara. Peraturan tersebut mengatur jaminan kesehatan bagi mantan menteri dan sekretaris kabinet beserta keluarganya, dengan biaya ditanggung oleh Anggaran Pendapatan dan Belanja Negara (APBN). Peraturan ini harus dikaji ulang mengingat Menteri Negara juga menerima pensiun sebagaimana tertuang dalam Peraturan Pemerintah Nomor 50 Tahun 1980 Pasal 10 yang berbunyi Menteri Negara yang berhenti dengan hormat dari jabatannya berhak memperoleh pensiun. Hal ini dapat menimbulkan diskriminasi karena masih banyak masyarakat, terutama di daerah terpencil dan perbatasan yang belum mendapatkan pelayanan kesehatan dasar salah satunya dikarenakan Anggaran untuk sektor kesehatan yang terbatas. Tujuan dari penilitian ini adalah untuk menganalisis politik hukum akibat terbitnya Peraturan Presiden Nomor 121 Tahun 2024 tentang Jaminan Pemeliharaan Kesehatan Purnatugas Menteri Negara dengan Metode pendekatan masalah yang digunakan oleh peneliti adalah yuridis normative dengan pendekatan pengkajian Perundang-undangan.Kata Kunci : Politik, Peraturan Presidan, Jaminan Pemeliharaan Kesehatan